Initial fluid resuscitation guided by the Parkland formula leads to high fluid volumes in the first 72 h, increasing mortality and the risk for kidney injury - Laura Lindahl; Tuomas Oksanen; Andrew Lindford; Tero Varpula (Burns Open, 2023)
Background: Our Burn center has used the Parkland formula (4 ml/kg/TBSA%) adjusted by physiological parameters to guide fluid resuscitation in burn patients. Our main objective was to examine fluid resuscitation in patients with major burn injury and its effect on mortality, need for renal replacement therapy (RRT) and the length of stay (LOS) in the Intensive Care Unit (ICU). Further aims were to determine which factors were associated with fluid resuscitation volumes during the first 24 h, and whether these fluid volumes had an association with the volumes infused during the next 48 h. Methods: This retrospective observational study accrued patients (N = 46) admitted to the Helsinki Burn Center between 2016 and 2018 with burn injuries ≥ 20% TBSA. The national intensive care registry and the electronic patient record system provided data on fluid infusions, urine output, laboratory measurements, presence of inhalation injury, surgical procedures within 72 h from injury, patient demographics, need for renal replacement therapy and mortality. Patients were divided into groups based on infused fluid volumes and univariate regressions were performed to identify factors associated with fluid volumes. Results: 48% of the patients received fluids more than 6 ml/kg/TBSA% during the first 24 h. 35% of the patients received fluid volumes exceeding the Ivy index (250 ml/kg/d) and was associated with higher TBSA%, SOFA and SAPS scores as well as increased mortality and need for RRT. Higher lactate and lower base excess were associated with higher fluid volumes. Urine output had no association with the resuscitation volumes. Larger resuscitation volumes during the first 24 h were associated with larger fluid volumes given also during the next 48 h. Higher cumulative fluid volume in 0–72 h resulted in increased need of RRT and higher ICU mortality. Conclusion: Using the Parkland formula and adjusting the infusion based on physiological parameters leads to over resuscitation in many of the patients. It seems that the more fluids are given during the initial resuscitation phase, the more fluids are also administered during the subsequent phase. Higher cumulative fluid volumes are associated with RRT requirements and higher mortality. We postulate that starting fluid resuscitation with a lower infusion rate could be beneficial, as it may lead to smaller cumulative fluid volumes during the first 72 h, leading to reduced mortality and kidney injury.